PERAN LITERASI MEMBACA DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Aning Tri Diastutik; Sabrun Jamil; Robiatul Adawiyah; M.Robby Salim; Siti Julhijjah; Indra Hambali; Hermansyah Surya Pratama; Muhammad Diki Saputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading literacy is a fundamental competence that plays an essential role in developing students’ critical thinking skills. Reading ability is not merely understood as the capacity to comprehend texts literally, but also includes the ability to analyze, evaluate, and synthesize information. This study aims to systematically examine the role of reading literacy in enhancing students’ critical thinking skills based on a literature review. The research method employed is library research by reviewing primary sources such as national and international journal articles, academic books, and relevant research reports. The findings indicate that reading literacy significantly contributes to the development of critical thinking skills through the enhancement of analytical abilities, argument evaluation, problem-solving, and reflective thinking. The integration of effective reading literacy strategies in learning processes has been proven to encourage students to become active and critical learners. Therefore, reading literacy plays a strategic role in supporting the achievement of 21st-century educational goals.